The Capability of Biochar-Based CaAl and MgAl Composite Materials as Adsorbent for Removal Cr(VI) in Aqueous Solution - Novie Juleanti; Neza Rahyu Palapa; Tarmizi Taher; Nurlisa Hidayati; Bunga Indah Putri; Aldes Lesbani (Science and Technology Indonesia, 2021)
The development of layered double hydroxide materials into composites with carbon-based materials in the form of CaAl-Biochar and MgAl-Biochar has been successfully carried out. The success parameters of the preparation process include XRD, FT-IR, Adsorption-Desorption N2, SEM, and TG-DTA. The success through XRD is evidenced by the appearance of the typical diffraction peaks of double-layer hydroxy around 2???? = 11°(003), 20°(006), and 60°(113). In addition, there is diffraction around 22°(002) which is the typical diffraction of biochar. FT-IR analysis showed successful preparation in the presence of functional groups around 1381cm−1 which indicated nitrate vibrations from double-layer hydroxy. Another spectrum that also appears on 1103 cm−1 is a characteristic of biochar (???? Si-O-Si). Adsorption-Desorption N2 analysis showed that the surface area data of 2 −1 2 −1 CaAl-Biochar was greater than MgAl-Biochar, which were 150.987 m .g and 111,404 m .g , respectively. The adsorption capacity of CaAl-Biochar reached 588.235 mg.g−1 and 426.316 mg.g−1 for MgAl-Biochar. The adsorbent materials of CaAl, MgAl, Biochar, CaAl-Biochar, and MgAl-Biochar tend to follow the Langmuir isotherm model with adsorption processes that tend to be spontaneous. The results of regeneration of the composite material lasted up to 5 cycles. The first cycle of CaAl-Biochar reached 96.647% to 82.666% in the last cycle, while MgAl-Biochar reached 90.885% in the first cycle to 73.454% in the last cycle.